Data-driven technique for analyzing the injector efficiency in a waterflooding operation. (August 2020) - Shabani, Ali; Moosavi, Mahdiyeh Sadat; Zivar, Davood; Jahangiri, Hamid Reza
Waterflooding is considered as one of the most common methods for improving the ultimate recovery of oil reservoirs. The efficiency of a waterflooding operation strongly depends on the determination and quantification of the relative connections between the injection and production wells. Injection and production rates are the most accessible data and they can provide useful information about the interwell connections. Recently, several data-driven approaches, such as the capacitance resistance model (CRM), have been presented based on available reservoir data. The CRM is a valuable analytical model for estimating the production rates and interwell connections through optimization of the production data. In this study, a CRM is used in order to estimate the production rate and evaluate the underground flow paths for both synthetic and real cases. A new concept called Value of Injection (VoI) is developed for the injectors to analyze their performance in the early time of the waterflooding prior to the significant water breakthrough. The calculated VoI is directly used for economical evaluation of the injectors. The results of this study show that a strong underground connection between an injector–producer pair does not always result in higher efficiency of the injector.